2022
DOI: 10.1111/cars.12376
|View full text |Cite
|
Sign up to set email alerts
|

Administrative data linkage in Canada: Implications for sociological research

Abstract: This paper explores some of the implications that administrative data, defined as data initially collected for purposes other than research, will have for Sociology. Although administrative data are “found” rather than “made” and, in turn, pose several challenges, we argue that the potential of these data warrant the investment, and may lead to a new methodological imagination that can shed a light on time‐tested concepts and advance our understanding of society. We show that it is already possible to advance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The present results are unique in that we compared the different sexual identity groups by cardiometabolic health risks and healthcare outcomes. In Canada and elsewhere, population data linkage studies are fostering valuable insights on the socioenvironmental determinants of health and healthcare use, although only a narrow subset of these have focused on cardiometabolic health disparities among sexual minority populations [ 1 , 13 ]. We found important unmet needs for primary care services among sexual minority groups, despite Canada’s universal healthcare system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present results are unique in that we compared the different sexual identity groups by cardiometabolic health risks and healthcare outcomes. In Canada and elsewhere, population data linkage studies are fostering valuable insights on the socioenvironmental determinants of health and healthcare use, although only a narrow subset of these have focused on cardiometabolic health disparities among sexual minority populations [ 1 , 13 ]. We found important unmet needs for primary care services among sexual minority groups, despite Canada’s universal healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…The use of record linkages across different types of datasets is becoming increasingly important in advancing the measurement and understanding of socio-spatial inequalities in health, especially among minority or hard-to-sample populations [ 1 , 2 , 3 , 4 ]. In several high-income countries, studies using representative surveys or administrative data alone (unlinked) have demonstrated disparities in mental health, psychiatric morbidity, and problematic substance use among sexual minorities, including lesbian, gay, and bisexual (LGB) adults [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This community forms links because its members engage in the same activities, perform the same type of work, and share similar duties. In contrast, a society characterized by organic solidarity exists precisely due to the disparities that exist within it, because everyone has various roles and duties (Yoshida et al, 2022).…”
Section: Social Solidaritymentioning
confidence: 99%
“…It must be emphasized that research conducted by computational sociologists needs to be guided by legal requirements, justice considerations, moral consciousness, and research ethics (McLevey, 2022; O'Neil, 2016; Tindall et al., 2022). Meanwhile, as the creation of administrative and digitized data (e.g., social media posts, newspaper articles, and tax records) is rarely intended for academic research (Yoshida et al., 2022), big data may entail big mistakes in data retrieving, compiling, and processing. Drawing on the preceding discussion, we now describe what sociologists in Canada and beyond may learn from the four studies in the themed section of big data and computational sociology.…”
mentioning
confidence: 99%
“…Sociologists and demographers in Canada will benefit greatly from Yoshida et al. (2022) sharing their expert knowledge and insights about the Canadian infrastructure of computational sociology and big data analytics. Based on the premise that administrative data are “found” rather than “made,” their conceptual definition of administrative data and informative discussion of data linkage projects help computational sociologists tap the hidden resources.…”
mentioning
confidence: 99%